Analysis of consistent soil–structure interface response in multi–directional shear tests by discrete element modeling. (September 2020) - Chen, Wei-Bin; Zhou, Wan-Huan; dos Santos, Jaime Alberto
Abstract: Structure surface normally owns highly directional properties caused by the properties of the material and the manufacturing process. Proper understanding of soil–structure interface behavior must recognize the structure surface's highly directional properties and take into consideration its interactions with particulate material. To investigate the mechanical behavior of granular soil–structure interface under multi–directional shear tests, a shear orientation is defined to be an angle θ between the shear direction and the principal rough direction of the directional surface. Using the discrete element method, a series of 3D numerical interface shear tests was conducted, under seven shear orientations ( θ  = 0°, 10°, 30°, 45°, 60°, 75°, and 90°). The consistent response of macroscale shear behavior at the interface, loaded by various shear orientations, are presented from the perspectives of the resultant average shear stresses in x – and y – directions and soil volumetric strain. A determination of the thickness of the localized shear band in each specimen is followed by the discussion of particle displacement vector distribution. Furthermore, the evolutions of microscale properties inside and outside the localized shear band, such as the coordination number and material fabric provide a physical meaning or an explanation for the consistent macroscale shear behavior of granular soil–structure interface at a microscale level. The findings emphasize the importance of measuring the horizontal load in x – and y – directions when conducting experimental interface shear tests on rough surface with highly directional properties, because the resultant resistance corresponds to the true resistance of the granular assembly.